Comparative study of joining methods for a SMART aerospace application - Chau, Eric T F (Cranfield University, 2007)
The adaptive serrated nozzle (ASN) is one of the most promising concepts to help reduce the noise level generated by aero-engines. Shear between a hot air stream and ambient air at the nozzle exit creates noise. The serrated nozzle is designed to protrude into the air stream causing mixing between the two air streams reducing the noise level. Adaptive control system using shape memory alloy (SMA) actuators deploy the protrusion only when required in order to maximise fuel efficiency. The successful joining of NiTi shape memory alloy (SMA) to the titanium parent structure is critical to the development of the adaptive serrated nozzle. However, joining of SMAs to dissimilar metals is widely known as extremely difficult if not impossible. This research provides a preliminary study into the potential of using SMAs in large engineering applications such as the ASN and the development of viable joining methods for joining SMA to titanium based alloy. Five most favourable conventional joining methods were selected for experimental investigation. Results proved that the successful joining of SMA to dissimilar alloys was extremely difficult, joint failures were mainly due to the formation of brittle intermetallics at joint interfaces. The formation of these intermetallics occurs irrespective of the type of joining method and level of heat input employed. However, it has been shown that the formation of these intermetallics can be suppressed by the manipulation of the joint composition. A marked improvement in joint performance has been achieved for joints that contained no more than 25 at% nickel. Joint improvement has also been achieved through the addition of titanium at the joint, although further research is necessary to investigate the effect of titanium addition to joint performance.